Integrating a Student Pharmacist Into the Home Healthcare Setting. (June 2016) - O'Neal, Fredrick; Frame, Tracy R.; Triplett, Julia
Abstract : Patients in a transition of care are highly susceptible to health and medication errors. In many situations, patients are eager to go home and providers are expected to discharge quickly. It is in this time of documented vulnerability that an increase in adverse effects related to poor health literacy, medication usage, and a lack of documentation occurs. Through the collaboration of Vanderbilt Home Care Services, Inc., and Belmont University College of Pharmacy, pharmacy students are utilized in a capacity that integrates pharmacy students into the home healthcare team to ease transitions of care and reduce medication-related problems in patients. Students work alongside home healthcare clinicians in both the field and the office to benefit patients the most by allowing each healthcare discipline to focus on what it does best.